An additional X‐ray diffraction by analyzer crystal. (17th June 2019) - Borkhodoev, V.Ya.
Abstract : In the X‐ray spectra of samples from the boric acid and rock, obtained using an X‐ray spectrometer with a wave dispersive, an unknown emission line with a wavelength shorter than the short‐wavelength border of the bremsstrahlung of the X‐ray tube was detected. The intensity and position of the line in the spectrum depend on the voltage on the X‐ray tube. It has been established that this line appears as a result of X‐ray diffraction from the atomic planes of the analyzer crystal, which are spaced from each other by two interplanar distances. Such diffraction was called additional X‐ray diffraction by analyzer crystal.